The Influence of the Microbiome on Anastomotic Leak - Boatman, Sonja; Kohn, Julia; Jahansouz, Cyrus (Clinics in Colon and Rectal Surgery, 2023)
Anastomotic leak, defined by the International Study Group of Rectal Cancer as “a communication between the intra- and extraluminal compartments owing to a defect of the integrity of the intestinal wall at the anastomosis,” is one of the most devastating complications in colorectal surgery. Much work has been done to identify causes of leak; however, despite advances in surgical technique, the prevalence of anastomotic leak has remained at around 11%. The potential causative role of bacteria in the etiopathology of anastomotic leak was established in the 1950s. More recently, alterations in the colonic microbiome have been shown to affect rates of anastomotic leak. Multiple perioperative factors that alter the homeostasis of the gut microbiota community structure and function have been linked to anastomotic leak after colorectal surgery. Here, we discuss the role of diet, radiation, bowel preparation, medications including nonsteroidal anti-inflammatory drugs, morphine, and antibiotics, and specific microbial pathways that have been implicated in anastomotic leak via their effects on the microbiome.
Keywords: anastomotic leak; colorectal surgery; microbiome; complications; prevention